2005
DOI: 10.1002/ajmg.b.30236
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that interaction between neuregulin 1 and its receptor erbB4 increases susceptibility to schizophrenia

Abstract: There is now strong evidence that Neuregulin 1 (NRG1) is a susceptibility gene for schizophrenia. NRG1 mediates some of its effects through the tyrosine kinase receptor erbB4, and analysis of gene knock-out animals suggests that the functional interaction of NRG1 and erbB4 mediates behaviors that may model some aspects of the schizophrenia phenotype in mice. Given these findings, we have sought evidence for association between schizophrenia and erbB4. Mutation screening of erbB4 in 14 DSMIV schizophrenics reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
140
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(144 citation statements)
references
References 28 publications
2
140
1
1
Order By: Relevance
“…The recent demonstration that loss of NRG1/ERBB4 signaling alters the tangential migration of cortical interneurons and reduces the number of GABAergic interneurons in post-natal cortex 38 is potentially a quite important mechanistic lead, since statistical evidence suggests that these two genes may synergistically increase the risk for schizophrenia. 39 The evidence of GABA dysfunction in schizophrenia is abundant. From circumstantial evidence of an association of schizophrenia with a lowered threshold for seizures, 40 recent studies have found direct evidence of impaired cortical inhibition (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The recent demonstration that loss of NRG1/ERBB4 signaling alters the tangential migration of cortical interneurons and reduces the number of GABAergic interneurons in post-natal cortex 38 is potentially a quite important mechanistic lead, since statistical evidence suggests that these two genes may synergistically increase the risk for schizophrenia. 39 The evidence of GABA dysfunction in schizophrenia is abundant. From circumstantial evidence of an association of schizophrenia with a lowered threshold for seizures, 40 recent studies have found direct evidence of impaired cortical inhibition (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Neuregulin-1 (NRG1) and its receptor, ErbB4, have been genetically linked to schizophrenia susceptibility Nicodemus et al 2006;Norton et al 2006;Silberberg et al 2006;Stefansson et al 2002) and are critical in neurodevelopment (Anton et al 2004;Ozaki et al 2000;Sardi et al 2006). Hence, NRG1 and ErbB4 are appealing molecules to study in schizophrenia, since this disease is hypothesized to have genetic and neurodevelopmental origins (Akbarian et al 1996;Eastwood and Harrison 2003;Jones et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] ERBB4 plays a critical role in the development of the brain, and has been shown to directly influence the proliferation, organization and migration of cells in the rostral migratory stream. [12][13][14] There is now emerging evidence that the gene for ERBB4 also influences risk for schizophrenia, 15,16 especially when considered together with NRG1. 16 Moreover, there is evidence from postmortem mRNA studies for alterations in the levels of ERBB4 15 (as well as the ERBB3 coreceptor [17][18][19][20][21] ) in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] There is now emerging evidence that the gene for ERBB4 also influences risk for schizophrenia, 15,16 especially when considered together with NRG1. 16 Moreover, there is evidence from postmortem mRNA studies for alterations in the levels of ERBB4 15 (as well as the ERBB3 coreceptor [17][18][19][20][21] ) in schizophrenia. A recent study that investigated neuregulin stimulation of ERBB4 in slices of prefrontal cortex from control and schizophrenic subjects demonstrated enhanced activation of ERBB4 by neuregulin in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%